Metaphor in Lyrics: How do Humans and Machines Interpret Maher Zain’s Insha Allah and Harris J’s Worth It Using Different Translation Techniques? - Nabilah, Fatihatul Haqi; Saehu, Andang; Ardiansyah, Erlan Aditya (Journal of English Language and Education, 2025)
Translation of metaphors in song lyrics presents a unique challenge, especially in the context of human versus machine translation. This study investigates how metaphors in Maher Zain’s Insha Allah and Harris J’s Worth It are interpreted and translated differently by human translators and machine translation tools such as Google Translate and DeepL. Using a descriptive qualitative approach with a comparative analysis method, this research identifies the translation techniques used and evaluates how effectively the metaphorical meanings and emotional tones are conveyed in both types of translations. The findings reveal that machine translators tend to translate metaphors literally, often missing cultural and emotional nuances. In contrast, human translators employ strategies like adaptation and paraphrasing to preserve implied meanings and emotional resonance. Furthermore, machine translation performs better on culturally universal metaphors but fails to accurately render idiomatic and emotionally rich metaphors. This study highlights the ongoing relevance of human translators in conveying metaphorical meaning in creative texts and contributes to the broader discourse on translation quality and technique in the age of artificial intelligence.